The comparison of roof visibility of the mandibular canal between cone-beam computed tomography scans and panoramic radiograph images as dependent on the cortical bone thickness of the mandible - Ali-Reza Ketabi; Angeliki Zelka; Hans-Christoph Lauer; Stefan Hassfeld (SpringerOpen, 2021)
Abstract Background Accurate detection of the mandibular canal is a difficult process despite cutting-edge radiographic methods. The present study analyses whether mandibular canal roof visibility is comparable to panoramic radiography (PR) and cone-beam computed tomography (CBCT) and, further, examines whether the visibility in PR and CBCT is dependent on cortical bone thickness in the mandible. Methods This study was conducted on a group of 343 selected patients. It incorporated anonymised data on 343 patients in which a CBCT and PR were available. The first stage examines whether the mandibular canal roof visibility is comparable to PR and CBCT. In the second stage, measurements of cortical bone thickness showed buccal and lingual in the P2, M1, M2 and M3 teeth areas, both to the left and right of the mandible in CBCT images. Statistical analysis was supported by statistical software (IBM SPSS 25; Armonk, NY, USA). Results The mean age of the patients was 58.8 years with an almost equal gender distribution. When performing a McNemar test on the P2, M1, M2 and M3 on both the left and right jaws, the difference between the two image modalities, with regard to the visibility of the canal roof, was found to be significant (McNemar test, p < 0.001). Statistically (U test, p≥0.05), it follows that the thickness of the cortical bone of the mandible exerts no influence on the visibility of the roof of canalis mandibulae in PR and CBCT images. Conclusion We conclude that the visibility of the mandibular canal in PR and CBCT rays is not identical, and that the thickness of the cortical bone in the mandible does not represent a factor affecting the visibility of the roof of the mandibular canal.